KEADAAN MEMAKSA (FORCE MAJEURE) SEBAGAI ALASAN PEMUTUSAN PERJANJIAN KERJA PEMAIN SEPAKBOLA PROFESIONAL DI PT SRIWIJAYA OPTIMIS MANDIRI - Suwastono, Hendro (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2017)
The Thesis Title Is "Force Majeure As A Reason Of Professional Football Player Employment Agreement Termination In PT Sriwijaya Optimis Mandiri". In This Research Formulated The Issue About The Criteria And Characteristics Of Force Majeure Condition  According To The Civil Law In Force In Indonesia, Which Can Be Used As A reason for termination of professional football player employment agreement in PT Sriwijaya Optimis Mandiri, is a termination of professional football player employment agreement have a fairness according to civil law in  Indonesia and why employment agreement was made itself and if there is any relevance and urgency if professional football player employment agreement made by Notary. To examine and answer problems mentioned above, this thesis using normative legal research that analyzed a legal enforceability, with legal materials, such as the research on the legal principles, positive law, legal rules, and rules of legal norms. Research use Legislation approach method (Statue Approach), Conceptual Approach and Case Approach. The research results indicate that criteria of force majeure which became the reason for termination of professional football players in PT Sriwijaya Optimis Mandiri is the state force due to policy or regulation. While its characteristics is a condition of force majeure are temporary, special, relative and temporer. Employment Agreement termination by reason of force majeure  that meets the Fairness, because the player can accept the decision and made no effort to remedy , The value of justice is seen in this case is a commutative justice values that are proportional, where players can understand the difficulty of management FC although they are also in unfavorable conditions, because there is no power that can not be avoided. Professional soccer player employment agreement made by itself because consideration is simpler, faster and more economically, while the idea of employment agreement made by Notary very relevant for professional soccer players should certainly be treated professionally also in making the employment agreement work performed by the Notary profession. However, the urgency remains dependent on the will of the parties (voluntary).